2007
DOI: 10.2308/iace.2007.22.3.391
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Group Response Systems on Student Satisfaction, Learning, and Engagement in Accounting Education

Abstract: We examine group response systems (GRS) as an educational tool. We use an experimental approach and student survey data to assess vendors' claims that GRS improve student engagement and feedback, and thus improve learning. A key part of our design involves controlling for effects of moving to a more interactive pedagogy that have been found to affect learning. For a management accounting course, we find only limited GRS learning effects, as proxied by exam performance. Contrary to our expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
1
17

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 12 publications
11
105
1
17
Order By: Relevance
“…Morse et al (2010) reported that students perceive that clicker use improved class discussion and made it more comfortable for students to participate in class. However, observation in the study supported previous findings by Carnaghan and Webb (2007) that indicated that students in clicker classes ask fewer questions and become more reliant on non-verbal communication.…”
Section: Literature Reviewsupporting
confidence: 81%
See 1 more Smart Citation
“…Morse et al (2010) reported that students perceive that clicker use improved class discussion and made it more comfortable for students to participate in class. However, observation in the study supported previous findings by Carnaghan and Webb (2007) that indicated that students in clicker classes ask fewer questions and become more reliant on non-verbal communication.…”
Section: Literature Reviewsupporting
confidence: 81%
“…Fitch (2004) and Beekes (2006) both found that students liked using clickers and found them to be a good active learning tool. Carnaghan and Webb (2007) indicated that students reported that the use of response systems technology improved their performance in class. In a four-year longitudinal study, Anderson and Noland (2010) found that remote response devices enable students to improve their knowledge and retain key concepts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hu et al, 2006) have found that engagement of students using clickers has a direct impact on their individual performance. There are studies that have either found no impact (e.g., Morling, McAuliffe, Cohen, & DiLorenzo, 2008) or negative impact (e.g., Carnaghan & Webb, 2007) of clickers use on students' engagement. Our experience also suggests that students who engage themselves constructively in the class using clickers are able to learn the lecture content better than those who do not bring it or use it during the class.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The use of technology can be beneficial to learning in groups and teams (Carnaghan & Webb, 2007;Clark & Gibb, 2006;Dineen, 2005;Hutchinson, 2007;Shrivastava, 1999;Williams, Duray, & Venkateshwar, 2006). In 1999, Shrivastava introduced the concepts of online learning communities to understand how university education can be organised to incorporate emerging digital and broadcasting technologies for classroom instruction and distance learning.…”
Section: Introductionmentioning
confidence: 99%